Seasonal climate forecasts and weekly agro-advisories disseminated via Laos Climate Services for Agriculture (LaCSA) changed field-level crop management practices of over 21,000 farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The Alliance provided technical support to the Strengthening Agro-climatic Monitoring and Information System (SAMIS) in Laos to develop tailored and validated agro-climatic advisories. These advisories were integrated into the Laos Climate Services for Agriculture (LaCSA) system which disseminates information to farmers through multiple channels. It is currently at the operational stage. About 21,140 farmers have already used the agro-climatic information to change such farming practices as crop variety, planting dates, and water and fertilizer applications.